The Schoolteachers' Version of the Stress and Anxiety to Viral Epidemics-9 (SAVE-9) Scale for Assessing Stress and Anxiety During the COVID-19 Pandemic - Yoo, Soyoung; Lee, Jihoon; Ju, Gawon; Lee, Sangha; Suh, Sooyeon; Chung, Seockhoon (Frontiers in Psychiatry, 2021)
This study aimed to validate the schoolteachers’ version of the Stress and Anxiety to Viral Epidemics-9 (SAVE-9) scale. This scale assessed the work-related stress of schoolteachers during the current pandemic. A total of 400 schoolteachers participated in an online survey between March 4 and 15, 2021. The survey questionnaire included the teachers’ version of the SAVE-9, Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorders-7 (GAD-7) scales. A screen test and parallel analysis suggested a single-factor structure model for the schoolteachers’ version of the SAVE-9 scale (real-data eigenvalue = 68.89, 95th percentile of the random eigenvalues = 27.56). The SAVE-9 scale showed good internal consistency (Cronbach’s alpha = 0.853) and good convergent validity with GAD-7 (rho = 0.545, p<0.001) and PHQ-9 (rho = 0.434, p<0.001) scale scores. Thus, teachers’ version of the SAVE-9 scale is a reliable and valid rating scale that can be applied to teachers in a pandemic situation.